A Novel Strategy for Selective O-Methylation of Glycerol in Subcritical Methanol - Bruniaux, Sophie; Varma, Rajender S.; Len, Christophe (Frontiers in Chemistry, 2019)
A new regioselective approach has been elaborated for the selective conversion of bio-based glycerol into the monomethyl derivative using sub/supercritical methanol. The reaction was realized in a batch process using three reactive components, namely, glycerol, methanol, and potassium carbonate to selectively produce the 3-methoxypropan-1,2-diol in mild yields; the mechanism of the O-methylation has been delineated using labeled methanol and GC-MS experiments.